2019
DOI: 10.1073/pnas.1904826116
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of the resilience of primary care networks by stress testing the health care system

Abstract: There are practically no quantitative tools for understanding how much stress a health care system can absorb before it loses its ability to provide care. We propose to measure the resilience of health care systems with respect to changes in the density of primary care providers. We develop a computational model on a 1-to-1 scale for a countrywide primary care sector based on patient-sharing networks. Nodes represent all primary care providers in a country; links indicate patient flows between them. The remova… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 29 publications
0
18
0
Order By: Relevance
“…There are now general texts on the subject [89][90][91][92][93][94][95][96] and research across subfields such as macroeconomics [97][98][99] , labour economics 100,101 , institutional economics 102 , environmental economics [103][104][105][106] , finance [107][108][109] , economics of disease transmission 110,111 , distribution of firms' sizes 112 , scaling laws 113,114 , ergodicity in economics 115 , technological innovation [116][117][118] and economic development 119 . If there are trends, they are towards more behavioural realism, grounding models on large data sets 120 , using computer experiments to study and design systems, and understanding how macro patterns emerge from micro assumptions.…”
Section: Some Frontiersmentioning
confidence: 99%
“…There are now general texts on the subject [89][90][91][92][93][94][95][96] and research across subfields such as macroeconomics [97][98][99] , labour economics 100,101 , institutional economics 102 , environmental economics [103][104][105][106] , finance [107][108][109] , economics of disease transmission 110,111 , distribution of firms' sizes 112 , scaling laws 113,114 , ergodicity in economics 115 , technological innovation [116][117][118] and economic development 119 . If there are trends, they are towards more behavioural realism, grounding models on large data sets 120 , using computer experiments to study and design systems, and understanding how macro patterns emerge from micro assumptions.…”
Section: Some Frontiersmentioning
confidence: 99%
“…2 Consequently indicators that seek to quantify the access to health care are often derived from these metrics, such as the number of care providers per capita in a given region 3 . It was recently shown that indicators such as the density of care providers fall short of capturing structural barriers to health care that arise from the fact that patients do not access physicians at random 4 . Rather, physicians are embedded in informal and emergent networks of flows of patients between them [5][6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, our role was to forecast how likely the 33% threshold of ICU beds being occupied by COVID-19 patients would be crossed within our forecast horizon. Our consortium consisted of three independent modelling teams with experience in the use and development of mathematical and computational models to address epidemiological and public health challenges [10][11][12][13][14][15][16]. The consortium was complemented with experts from the Ministry of Health, the Austrian Agency for Health and Food Safety, as well as external public health experts in weekly meetings.…”
Section: Introductionmentioning
confidence: 99%